The Effects of a Work-Related Musculoskeletal Disorder Prevention Model for Health Personnel in Ranong Province. - Tipyan, Natwalan; Wongsakoonkan , Watcharaporn; Sillaparasamee, Ratthapol; Chusak, Thassaporn (Health Science Journal of Thailand, 2025)
This quasi-experimental study aimed to evaluate the effects of a prevention model for work-related musculoskeletal disorders (WMSDs) among 30 health personnel in Ranong Province. Research tools included a questionnaire, the Rapid Office Strain Assessment (ROSA), and the Standardized Nordic Questionnaire. Data were analyzed using descriptive statistics, including frequency, percentage, mean, and standard deviation, and inferential statistics, including Paired Sample T-tests, to compare mean scores of muscle pain before and after the intervention. The findings revealed that most participants were female (80.00%), aged 30–39 years (40.00%), worked 7–9 hours daily, and had over 21 years of work experience. Additionally, 53.30% reported normal stress levels. Most of the sample (76.70%) worked primarily in office settings. After implementing the prevention model, the overall mean scores for risk behaviors associated with WMSDs significantly decreased (p-value < 0.05). Additionally, musculoskeletal symptoms in various body parts were significantly reduced after performing the Manee Vej exercise (p-value < 0.05). The findings of this research can be applied to individuals experiencing work-related muscle pain, including those in government agencies and office employees, enabling them to manage and alleviate pain independently as an initial self-care measure.